Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 130089 by ajfour last updated on 22/Jan/21

To solve   x^3 =x+c  Let  y=(x−p)(x^3 −x−c)    (dy/dx)=(x^3 −x−c)+(3x^2 −1)(x−p)    let   (dy/dx)=mx  ⇒  (3x^2 −1)(x−p)=mx  3x^3 −3px^2 −(m+1)x+p=0  3(x+c)−3px^2 −(m+1)x+p=0  3px^2 +(m−2)x−(3c+p)=0  and since x^3 =x+c  (m−2)x^2 +(2p−3c)x+3cp=0  [9cp^2 +(3c+p)(m−2)]x  +[3cp(m−2)+(3c+p)(2p−3c)]  =0  x=−(((3c+p)(2p−3c)+3cp(m−2))/(9cp^2 +(3c+p)(m−2)))  (m−2)x^2 +(2p−3c)x+(3cp)=0  Now choosing suitable ′p′ value  we find ′m′;  and then x=f(p,m) ★

Tosolvex3=x+cLety=(xp)(x3xc)dydx=(x3xc)+(3x21)(xp)letdydx=mx(3x21)(xp)=mx3x33px2(m+1)x+p=03(x+c)3px2(m+1)x+p=03px2+(m2)x(3c+p)=0andsincex3=x+c(m2)x2+(2p3c)x+3cp=0[9cp2+(3c+p)(m2)]x+[3cp(m2)+(3c+p)(2p3c)]=0x=(3c+p)(2p3c)+3cp(m2)9cp2+(3c+p)(m2)(m2)x2+(2p3c)x+(3cp)=0Nowchoosingsuitablepvaluewefindm;andthenx=f(p,m)

Commented by bobhans last updated on 22/Jan/21

example : x^3 =x+6  y=(x−p)(x^3 −x−6)  (dy/dx) = x^3 −x+6+(x−p)(3x^2 −1)  (dy/dx)= 4x^3 −4px^2 −2x+p+6  (dy/dx)=4x+24−4px^2 −2x+p+6=2x−4px^2 +30+p  let (dy/dx) = mx ⇒4px^2 +(m−2)x−(p+30)=0  x=((2−m±(√((m−2)^2 +16p(p+30))))/(8p))  now  { ((p=?)),((m=?)) :}

example:x3=x+6y=(xp)(x3x6)dydx=x3x+6+(xp)(3x21)dydx=4x34px22x+p+6dydx=4x+244px22x+p+6=2x4px2+30+pletdydx=mx4px2+(m2)x(p+30)=0x=2m±(m2)2+16p(p+30)8pnow{p=?m=?

Commented by ajfour last updated on 23/Jan/21

Answered by ajfour last updated on 23/Jan/21

x=−(((3c+p)(2p−3c)+3cp(m−2))/(9cp^2 +(3c+p)(m−2)))  (m−2)x^2 +(2p−3c)x+(3cp)=0  say  m−2=M  x=−((3cpM+(3c+p)(2p−3c))/((3c+p)M+9cp^2 ))  let  (M/p)=s  ,  (1/p)=q     x=−((3cs+(3cq+1)(2−3cq))/((3cq+1)s+9c))  s[3cs+(3cq+1)(2−3cq)]^2   −(2−3cq)[3cs+(3cq+1)(2−3cq)][(3cq+1)s+9c]  +3c[(3cq+1)s+9c]^2 =0    9c^2 s^3 +6c(3cq+1)(2−3cq)s^2   +(3cq+1)^2 (2−3cq)^2 s_(−)   −6c(3cq+1)s^2 −54c^2 s  +9c^2 q(3cq+1)s^2 +81c^3 qs  −(3cq+1)^2 (2−3cq)^2 s_(−)   −9c(3cq+1)(2−3cq)^2   +3c(3cq+1)^2 s^2 +54c(3cq+1)s  +243c^3 =0  ⇒  (9c^2 )s^3 +[6c(3cq+1)(2−3cq)    −6c(3cq+1)+9c^2 q(3cq+1)    +3c(3cq+1)^2 ]s^2 +     [54c^2 +81c^3 q+54c(3cq+1)]s  +[−9c(3cq+1)(2−3cq)^2 +243c^3 ]=0  let  q=0  ⇒  s^3 +(1/c)s^2 +6((1/c)+1)s               −((4/c)−27c)=0  s=−2.54409 , −0.95044  for c=((30)/(19(√(19))))     x=−((3cs+(3cq+1)(2−3cq))/((3cq+1)s+9c))  and for  q=0    x=−((3cs+2)/(s+9c)) =   right answer is x=1.14708

x=(3c+p)(2p3c)+3cp(m2)9cp2+(3c+p)(m2)(m2)x2+(2p3c)x+(3cp)=0saym2=Mx=3cpM+(3c+p)(2p3c)(3c+p)M+9cp2letMp=s,1p=qx=3cs+(3cq+1)(23cq)(3cq+1)s+9cs[3cs+(3cq+1)(23cq)]2(23cq)[3cs+(3cq+1)(23cq)][(3cq+1)s+9c]+3c[(3cq+1)s+9c]2=09c2s3+6c(3cq+1)(23cq)s2+(3cq+1)2(23cq)2s6c(3cq+1)s254c2s+9c2q(3cq+1)s2+81c3qs(3cq+1)2(23cq)2s9c(3cq+1)(23cq)2+3c(3cq+1)2s2+54c(3cq+1)s+243c3=0(9c2)s3+[6c(3cq+1)(23cq)6c(3cq+1)+9c2q(3cq+1)+3c(3cq+1)2]s2+[54c2+81c3q+54c(3cq+1)]s+[9c(3cq+1)(23cq)2+243c3]=0letq=0s3+1cs2+6(1c+1)s(4c27c)=0s=2.54409,0.95044forc=301919x=3cs+(3cq+1)(23cq)(3cq+1)s+9candforq=0x=3cs+2s+9c=rightanswerisx=1.14708

Terms of Service

Privacy Policy

Contact: info@tinkutara.com